A 3D printed device for quantitative enzymatic detection using cell phones. Issue 32 (26th July 2016) - Comina, G.; Suska, A.; Filippini, D.
Abstract : General enzymatic detection with cell phones using 3D printed fluidics and optics. Abstract : A disposable device for quantitative enzymatic detection capable of coupling illumination and image readouts from cell phones is demonstrated. The device integrates a calibration range for glutamate detection, utilizes the phone screen as a light source, and provides the necessary actuation for autonomous operation. Custom made optics required to couple to the cell phone camera is accomplished using affordable stereolithography (SLA) 3D printers. The described method does not involve polishing, requires only two steps from design to implementation, and can be locally applied to 3D printed lab-on-a-chip (LOC) prototypes, using the same materials. Optical finishing and dimensional variability within 2% were achieved, supporting entirely arbitrary geometries for elements larger than 400 μm in radius. Representative fabrication times and costs were 20 min and 0.50 USD per prototype.